2019
DOI: 10.1163/22941932-40190257
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of anatomical structure of tension wood among 242 tropical tree species

Abstract: Angiosperm trees produce tension wood to actively control their vertical position. Tension wood has often been characterised by the presence of an unlignified inner fibre wall layer called the G-layer. Using this definition, previous reports indicate that only one-third of all tree species have tension wood with G-layers. Here we aim to (i) describe the large diversity of tension wood anatomy in tropical tree species, taking advantage of the recent understanding of tension wood anatomy and (ii) explore any lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Our frequent observations of extraxylary G‐fibers complement recent findings that extraxylary tissues play important roles in movements that were previously attributed solely to xylem. For example, experiments on artificially inclined trees demonstrated that bark also influences plant posture (Ghislain et al ., 2019a,b), and Lehnebach et al . (2020) showed that phloem G‐fibers arranged in a trellis network produce higher tensile stress than species with a phloem trellis network of ordinary fibers do.…”
Section: Testing the Relationship Between Liana Climbing Mechanisms A...mentioning
confidence: 91%
“…Our frequent observations of extraxylary G‐fibers complement recent findings that extraxylary tissues play important roles in movements that were previously attributed solely to xylem. For example, experiments on artificially inclined trees demonstrated that bark also influences plant posture (Ghislain et al ., 2019a,b), and Lehnebach et al . (2020) showed that phloem G‐fibers arranged in a trellis network produce higher tensile stress than species with a phloem trellis network of ordinary fibers do.…”
Section: Testing the Relationship Between Liana Climbing Mechanisms A...mentioning
confidence: 91%
“…11). 3), two species had a lignified G layer (Eschweilera & Qualea), one a peculiar multilayered G layer (Laetia) and three no G layer fibre (Jacaranda, Virola, Simarouba), according to a recent classification based on 242 tropical species (Ghislain et al 2019). Measurement of MFA on the 3 species represented in Fig.…”
Section: Specific Behaviour Of Reaction Woodmentioning
confidence: 99%
“…Figure 12. Comparative anatomy of compression wood and normal wood for the conifer species CW: compression wood; NW: normal woodFor hardwoods, a majority of G-layer type TW (3 poplars, Miconia, Carapa, Ocotea, Cecropia, Eperua) were studied (Table3), two species had a lignified G layer (Eschweilera & Qualea), one a peculiar multilayered G layer (Laetia) and three no G layer fibre (Jacaranda, Virola, Simarouba), according to a recent classification based on 242 tropical species(Ghislain et al 2019). Measurement of MFA on the 3 species represented in Fig.13(Ruelle et al 2007) showed lower values for TW (2° to 14°) than for NW (10° to 35°), with some overlap around 10°-14°.…”
mentioning
confidence: 99%
“…For extended axial tensile stress generation, most hardwoods form tension wood fibers, which possess a characteristic G‐layer, which can be structurally very diverse, as recently investigated for tropical tree species. [ 57 ] The G‐layer is an additional layer, which can fill the entire lumen of the tension wood fiber (Figure 2 tension wood microscopy image and schematics and Figure 4E) and consists in many trees of almost pure cellulose with a microfibril angle of ≈0°. This results in an extremely high axial stiffness, which is beneficial for high tensile stresses, but only if a certain contractibility is allowed at the same time.…”
Section: Structure Of Plant Cell Walls and The Storage Of Informationmentioning
confidence: 99%